ITO 박막의 공정변수에 따른 특성 연구 - 김소라(So-Ra Kim); 서정은(Jung-Eun Seo); 김상호(Sang-Ho Kim) (Biuletyn Uniejowski, 2004)
ITO thin film was deposited on the glass by RF magnetron sputtering. Dependance of the process parameters such as thickness, target-to-substrate distance, substrate temperature and oxygen partial pressure on the transmittance and electrical resistance of ITO film were investigated. The deposition conditions for getting better optical and electrical ITO characteristics were the 1800-$2300Å$ thickness, 65mm substrate-to-target distance, $350^{°}C$ substrate temperature and 8% oxygen partial pressure. At these conditions, the transmittance and sheet resistance of the ITO film were 83.3% and 77.86Ω/$\square$, respectively.